Impact of aggression, depression, and anxiety levels on quality of life in epilepsy patients - Izci F; Fındıklı E; Camkurt MA; Tuncel D; Şahin M (Neuropsychiatric Disease and Treatment)
Filiz Izci,1 Ebru Fındıklı,2 Mehmet Akif Camkurt,3 Deniz Tuncel,4 Merve Şahin2 1Department of Psychiatry, School of Medicine, Istanbul Bilim University, Istanbul, 2Department of Psychiatry, School of Medicine, Sütçü İmam University, 3Department of Psychiatry, Afşin State Hospitale, 4Department of Neurology, School of Medicine, Sütçü İmam University, Kahramanmaraş, Turkey Abstract: The aim of this study was to investigate the impact of aggression levels on the quality of life (QoL) of epilepsy patients. This study was conducted on 66 volunteer control subjects, who were matched by age and sex to the patient group, which consisted of 66 patients who applied to the Psychiatry and Neurology clinics for outpatient treatment, were aged between 18 years and 65 years, and were diagnosed with epilepsy. A sociodemographic and clinical data form designed by us was distributed among the study participants, along with Buss–Perry Aggression Scale, Beck Anxiety Scale, Beck Depression Scale, and the Quality of Life Scale Short Form (SF-36). Compared with the control group, the patient group displayed higher scores in all subgroups of Buss–Perry Aggression Scale subscales at a statistically significant level (P<0.05). As per the SF-36 questionnaire, physical functioning, physical role disability, general health perception, social functioning, mental health perception, and pain subscales were statistically lower in the patient group (P<0.05). Significant links between Beck Depression Scale and Beck Anxiety Scale levels, as well as some subscales of QoL and aggression levels, were also determined. In conclusion, epilepsy patients experienced impaired QoL compared with the healthy control group and their QoL was further impaired due to increased levels of anxiety, depression, and aggression. Keywords: aggression, depression, anxiety, quality of life, epilepsy